Coding race: Playing with algorithms - Rizk, Nadya; McKenzie, Matt; Samrout, Marya (Teaching science (Deakin West, A.C.T.), 2022)
Coding is a process often associated with computers. Nevertheless, coding is a thought process that can be mastered even without a computer. In NSW, primary students are introduced to computational and algorithmic thinking as early as Stage 1. Yet, teaching coding to young students is not always easy for teachers, mostly because the process is often invisible and abstract. The activity described here offers one way to teach coding to primary students in a fun, interactive, and stimulating environment. More importantly, it incorporates a play-based approach to engage students with the concrete skills of coding and to expand their views about algorithms and codes.